2021
DOI: 10.1038/s41467-021-26873-w
|View full text |Cite
|
Sign up to set email alerts
|

Laughlin anyon complexes with Bose properties

Abstract: Two-dimensional electron systems in a quantizing magnetic field are regarded as of exceptional interest, considering the possible role of anyons—quasiparticles with non-boson and non-fermion statistics—in applied physics. To this day, essentially none but the fractional states of the quantum Hall effect (FQHE) have been experimentally realized as a system with anyonic statistics. In determining the thermodynamic properties of anyon matter, it is crucial to gain insight into the physics of its neutral excitatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The authors of the paper observed analogous abnormal optical transitions in the spectrum of spin density neutral excitations for the main Laughlin state 1/3, measured by the resonant reflection for several heterostructures with GaAs/AlGaAs quantum wells [5,26,27]. The spectrum indicates the direct optical transitions that excite spin birotons (spin magnetogravitons), as well as the transitions that give rise to excitations with the energy lying in the bandgap of the fractional Hall dielectric ν = 1/3 (Figure 3).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…The authors of the paper observed analogous abnormal optical transitions in the spectrum of spin density neutral excitations for the main Laughlin state 1/3, measured by the resonant reflection for several heterostructures with GaAs/AlGaAs quantum wells [5,26,27]. The spectrum indicates the direct optical transitions that excite spin birotons (spin magnetogravitons), as well as the transitions that give rise to excitations with the energy lying in the bandgap of the fractional Hall dielectric ν = 1/3 (Figure 3).…”
Section: Discussionmentioning
confidence: 78%
“…The spectrum indicates the direct optical transitions that excite spin birotons (spin magnetogravitons), as well as the transitions that give rise to excitations with the energy lying in the bandgap of the fractional Hall dielectric ν = 1/3 (Figure 3). Unlike birotons, which exhibit bosonic properties predicted for neutral excitations [5], the anomalous excitations do not show signs of Bose statistics [26,27], suggesting possible transitions between the ground states of different fractional states rather than neutral excitations in the fractional QHE state 1/3.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations